DEVELOPMENT MANAGEMENT TRANSFER PRICING BY APPLICATION OF THE INTERVAL ESTIMATES - Elena B. Shuvalova; Olga S. Platoshkina (Статистика и экономика)
The article discusses the application of the method of interval estimation of conformity of the transaction price the market price. A comparative analysis of interval and point estimate. Identified the positive and negative effects of using interval estimation.